2013
DOI: 10.1016/j.molcel.2013.08.047
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear Pore Regulates GAL1 Gene Transcription by Controlling the Localization of the SUMO Protease Ulp1

Abstract: Transcription activation of some yeast genes correlates with their repositioning to the nuclear pore complex (NPC). The NPC-bound Mlp1 and Mlp2 proteins have been shown to associate with the GAL1 gene promoter and to maintain Ulp1, a key SUMO protease, at the NPC. Here, we show that the release of Ulp1 from the NPC increases the kinetics of GAL1 derepression, whereas artificial NPC anchoring of Ulp1 in the Δmlp1/2 strain restores normal GAL1 regulation. Moreover, artificial tethering of the Ulp1 catalytic doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(103 citation statements)
references
References 67 publications
5
98
0
Order By: Relevance
“…In addition, budding yeast Ulp1 was recently shown to desumoylate transcription factors on chromatin to facilitate transcriptional activation, providing an example of recruitment of Ulp1 targets to the nuclear pore (50). Interestingly, a subcomplex of the human nuclear pore including Nup133 transiently localizes to centromeres and contributes to their mitotic function (55).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, budding yeast Ulp1 was recently shown to desumoylate transcription factors on chromatin to facilitate transcriptional activation, providing an example of recruitment of Ulp1 targets to the nuclear pore (50). Interestingly, a subcomplex of the human nuclear pore including Nup133 transiently localizes to centromeres and contributes to their mitotic function (55).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study showed that Ulp1, an NPCassociated SUMO protease, accelerates derepression of the prototypical GAL1 gene, which migrates to NPCs during induction (Texari et al 2013). This scenario and others in which tDNAs associate with NPCs for reasons other than export are distinct because, in these cases, pretRNAs generated at the NPC might venture elsewhere in the nucleus before subsequent export.…”
Section: Potential Advantages Of Tdna Transcription At Npcsmentioning
confidence: 99%
“…After six months, it is available under a Creative Commons License (Attribution-NonCommercial 4.0 International), as described at http:// creativecommons.org/licenses/by-nc/4.0/. initial transcriptional induction as well as transcriptional reactivation (Hampsey et al 2011;Texari et al 2013).…”
mentioning
confidence: 99%
“…In addition to the main function of the Nups in nucleocytoplasmic transport, new roles -especially in the regulation of gene expression -have recently been identified (Texari et al, 2013;Van de Vosse et al, 2013). Therefore, it is not surprising that aberrant functions of Nups and NPCs have been implicated in many and diverse human pathologies, including autoimmune diseases, viral infections, cardiomyopathies and various cancers (Capelson and Hetzer, 2009;Chow et al, 2012;Hatch and Hetzer, 2014;Simon and Rout, 2014).…”
Section: Perspectivesmentioning
confidence: 99%